Phytochemicals in the treatment of patients with depression: a systemic review - Natalia Picheta; Julia Piekarz; Karolina Daniłowska; Karol Mazur; Halina Piecewicz - Szczęsna; Agata Smoleń (Frontiers in Psychiatry)
BackgroundDepression is a complex mental disease whose incidence increases every year; 300 million people worldwide currently suffer from it. Women are more likely to suffer from depression, twice the rate as men. It is one of the few illnesses that can lead to suicide, which makes it very dangerous – currently, 700,000 people die from suicide and it is the 4th most common cause of death in people aged 15-29. The treatment strategies for depression is a big challenge for physicians, pharmacists, scientists and classic remedies cause many side effects. Therefore, natural phytotherapy with herbs can prove to be a good solution. Phytotherapy is a popular treatment method used for centuries in Chinese medicine or Ayurveda.Materials and methodsThe study conducted a comprehensive database search PubMed, ClinicalKey and MedNar covered the years 2015 - 2024 to provide the most up-to-date data. 13 randomized controlled trials and 1 meta – analysis were included in the systematic review.ResultsMany plants show anti-inflammatory, antioxidant and cognitive enhancing effects, which are particularly important in depression. In the treatment of depression, plants such as Crocus sativus L. stigma, Lavandula angustifolia, Hypericum perforatum L. and Curcuma longa L. have proven to be effective. They show good effectiveness in human studies and alleviate the symptoms of depression. Herbal products can support classical pharmacotherapy, but this requires further research. Non-commercial clinical trials in the future should provide answers to research questions: at what stage of treatment of patients with MDD will the use of phytochemicals be most appropriate in terms of therapy efficacy and safety for the patient.ConclusionsCrocus sativus L. stigma, Lavandula angustifolia, Hypericum perforatum L. and Curcuma longa L. in modern medicine can help improve the well-being of patients with depression. The use of herbs as an intervention was associated with a decrease in the concentration of proinflammatory cytokines and an overall improvement in the mood of patients. Further research should be undertaken into combining both therapies in order to improve patients’ quality of life and reduce treatment costs.